Characteristics of Extended-Spectrum Beta-Lactamase-Producing Enterobacteriaceae and Contact to Animals in Estonia - Telling, Kaidi (Microorganisms, 2020)
We have attempted to define the prevalence and risk factors of extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-Enterobacteriaceae) carriage, and to characterize antimicrobial susceptibility, beta-lactamase genes, and major types of isolated strains in volunteers, with a specific focus on humans in contact with animals. Samples were collected from 207 volunteers (veterinarians, pig farmers, dog owners, etc.) and cultured on selective agar. Clonal relationships of the isolated ESBL-Enterobacteriaceae were determined by whole genome sequencing and multi-locus sequence typing. Beta-lactamases were detected using a homology search. Subjects filled in questionnaires analyzed by univariate and multiple logistic regression. Colonization with ESBL-Enterobacteriaceae was found in fecal samples of 14 individuals (6.8%; 95%CI: 3.75–11.09%). In multiple regression analysis, working as a pig farmer was a significant risk factor for ESBL-Enterobacteriaceae carriage (OR 4.8; 95%CI 1.2–19.1). The only species isolated was Escherichia coli that distributed into 11 sequence types. All ESBL-Enterobacteriaceae isolates were of CTX-M genotype, with the blaCTX-M-1 being the most prevalent and more common in pig farmers than in other groups. Despite the generally low prevalence of ESBL-Enterobacteriaceae in Estonia, the pig farmers may still pose a threat to transfer resistant microorganisms. The clinical relevance of predominant blaCTX-M-1 carrying E. coli is still unclear and needs further studies.